Degradasi Senyawa Organik pada Palm Oil Mill Secondary Effluent Menggunakan Fotokatalis TiO2 - Indriana Lestari (Politeknik Kelapa Sawit Citra Widya Edukasi, 2017)
Degradation of organic compound on palm oil mill secondary effluent by photocatalytic process using TiO2 photocatalysts with aeration of air has been carried out in the semi batch photo-reactor system equipped with mercury 350 W lamps. The concentration of organic compounds in POMSE was analyzed by UV-Vis Spectrophotometer. Photodegradation performance test showed that TiO2 photocatalyst was able to degrade organic compounds and could eliminate phenol pollutans in POMSE effectively, where the degradation performance of organic compound from TiO2 photocatalyst was respectively 31.36% and phenol elimination up to 96.66% (loading TiO2 = 1.5 g/L, air flow rate = 10 cc/min) at minutes-120. The result also showed that the performance of TiO2 photocatalyst in degrading organic compound was stable at 25.25 to 31.36% for two hours (COD POMSE of 250 to 650 ppm).